Development of strain hardening cementitious composite (SHCC) reinforced with 3D printed polymeric reinforcement: Mechanical properties. (1st October 2019) - Xu, Yading; Šavija, Branko
Abstract: Cracking in concrete needs to be limited for esthetical and durability reasons. Currently, this is commonly done by using steel rebars in the structure or fiber reinforcement in the material. With certain fiber types and micromechanical design, it is even possible to create cement-based materials with steel like (i.e. quasi-plastic) properties – so called strain hardening cementitious composites (SHCCs). In this paper, an alternative approach for creating SHCC – through use of additive manufacturing to create polymeric reinforcement meshes – is proposed. Different designs are manufactured, casted in the cementitious matrix, and tested in four-point bending and uniaxial tension. It was found that, with proper designs, it is possible to create cementitious composites with deflection hardening or strain hardening properties. Furthermore, with proper design, multiple cracking behavior of conventional SHCC can be replicated. In addition, numerical simulations were performed using the Delft lattice model. Four point bending tests on mortar bars reinforced by two different mesh designs were simulated and the results show good agreement with the experiments. This research shows great potential of using additive manufacturing for creating SHCCs with customizable properties.